Geopolitical risks, GDP and tourism: An ARDL-ECM cointegration study on Ukraine - Olena Stryzhak; Ramazan Sayar; Yılmaz Onur Ari\. (CES Working Papers, 2022)
Tourism is a sector of the economy that is significantly affected by fluctuations in economic and political activity and the influence of external factors. Political tensions with Russia and the Crimean issue have affected tourism revenues as well as Ukraine's economic growth. Therefore, the situation in the Ukrainian tourism sector requires the development of science-based approaches and practical advice to improve tourism in Ukraine, taking into account the impact of environmental risks. In the study, the long-term effect of Ukraine's GDP and GPR Index on Ukrainian tourism was investigated for the period 1995-2019. The ARDL Boundary Test is used in the analysis to explore the long-term impact of Ukraine's GDP and GPR on Ukrainian tourism. ADF by Dickey and Fuller, and Phillips Perron unit root tests are used to assess the degree of integration of the series. Empirical findings suggest that geopolitical risk has a negative impact on tourism revenues. Results of research support the initial hypothesis that there is a nexus among indicators of economic growth, tourism, and the GPR index. This gives grounds for the assertion that reducing the level of risk to a minimum will increase the attractiveness of Ukraine as a tourist destination, thereby creating new opportunities for economic growth and social development.
Keywords: 330; geopolitical risk; GPR Index; economic growth; tourism; ARDL cointegration; Ukrainiantourism